Automation of Aluminium Smelting Pot Cover Handling - Early Stage Development of a Customised Gripper Tool and a Manipulator Concept Review for Automation of a Primary Aluminum Potroom Process - Jørs, Even (NTNU, 2020)
Redistribution of cover mass is an aluminium potroom operation which is straining upon the workers at Alcoa Mosjøen. Though it is unpopular to perform, it is very much required for the production of top quality primary aluminium. A future goal for Alcoa is to substitute the current manual process with an automated guided vehicle (AGV), capable of performing the operation semi or completely autonomously. This thesis describes the early stage development of a subsystem for this vehicle. The thesis objective is set to automate inside access to the smelting pots. This is acquired through gripping, handling and storing of removable hatches. To provide task automation, a system consisting of a robotic manipulator and a specialised gripper tool has been developed. From the gripper development, a high-resolution aluminium prototype has been created. The prototype is capable of gripping, handling and storing of pot hatches securely through a mechanical self-clamping mechanism. With a purely mechanical gripper concept, Alcoa is provided with a robust, easily maintainable and energy independent gripping solution. Through robot research, the possibility of exploiting the AGV propulsion along the pot has been identified. This has led to a 2-axis articulated robot concept, stationary placed on the AGV platform. Through scaled down testing of the robot and gripper system, dual simultaneous cover handling has been achieved. Further research has confirmed that off-the-shelf robot solutions exist, fulfilling the specific attributes required for AGV implementation. Feedback from Alcoa states conviction of system feasibility, and a kick-start of the automation project has been initiated as a result.